EXECUTIVE SUMMARIES OF TEACHER’S ABILITY ON TPACK IN NORTH SUMATERA: PRELIMINARY RESEARCH ON THE DEVELOPMENT OF SCIENCE LITERACY-BASED LEARNING MODELS - Jamalum Purba; Mariati P Simanjuntak; Ely Djulia; Halim Simatupang; Aristo Hardinata (ISER (Indonesian Science Education Research), 2023)
To be able to teach scientific literacy to students, teachers need scientific literacy competencies and are in line with TPACK (Technological Pedagogical Content Knowledge) competencies. This research was initial research in the development of learning models which aims to determine the extent of the TPACK abilities of science teachers in North Sumatra. The method used in this study was a qualitative descriptive method by describing data in the form of numbers and direct interviews. The instrument used was TPACK multiple choice questions that had been previously developed and proven valid to be able to measure the TPACK ability of science teachers which consisted of 40 questions. The research sample was determined by purposive sampling method. From the sampling results, 20 science teachers were selected from 10 junior high schools in North Sumatra